1987
DOI: 10.1016/s0735-1097(87)80309-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the bioenergetics of cardiac allograft rejection using in vivo P-31 nuclear magnetic resonance spectroscopy

Abstract: Monitoring human cardiac allograft rejection is currently accomplished by endomyocardial biopsy. Available noninvasive methods for identifying rejection have lacked the necessary sensitivity or specificity, or both, for routine clinical application. In vivo phosphorus-31 (P-31) nuclear magnetic resonance (NMR) spectroscopy has been used for monitoring phosphorus metabolism in both animal models and humans. In the present study this technique was employed as a noninvasive means to assess the bioenergetic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…377 Taken together, these results suggest that CMR spectroscopy can provide metabolic evidence for myocardial viability. 365 In early cardiac allograft rejection, decreased PCr/ATP ratios are seen, 378,379 although this must be distinguished from transient reductions early after transplantation that might occur on the basis of transient allograft ischaemia. In LV hypertrophy, the PCr/ATP ratio is generally normal, 380 but reductions are seen in hypertrophic cardiomyopathy.…”
Section: Prosthetic Valvesmentioning
confidence: 99%
“…377 Taken together, these results suggest that CMR spectroscopy can provide metabolic evidence for myocardial viability. 365 In early cardiac allograft rejection, decreased PCr/ATP ratios are seen, 378,379 although this must be distinguished from transient reductions early after transplantation that might occur on the basis of transient allograft ischaemia. In LV hypertrophy, the PCr/ATP ratio is generally normal, 380 but reductions are seen in hypertrophic cardiomyopathy.…”
Section: Prosthetic Valvesmentioning
confidence: 99%
“…Taken together, these results suggest that CMR spectroscopy can provide metabolic evidence for myocardial viability (Bottomley and Weiss, 1998). In early cardiac allograft rejection, decreased PCr/ATP ratios are seen (Canby et al, 1987;Fraser et al, 1990), although this must be distinguished from transient reductions early after transplantation that might occur on the basis of transient allograft ischaemia. In LV hypertrophy, the PCr/ATP ratio is generally normal (Pluim et al, 1996), but reductions are seen in hypertrophic cardiomyopathy (Jung et al, 1998;Rajagopalan et al, 1987).…”
Section: Cardiovascular Magnetic Resonance Spectroscopymentioning
confidence: 92%
“…Canby et al (14) were responsible for a study published in the Journal of the American College of Cardiology in which they demonstrated that the 31 P NMR spectroscopy-determined phosphocreatine/adenosine triphosphate ratio was inversely related to the severity of histologically demonstrated cardiac allograft rejection in a rat model. This relationship suggested that in vivo 31 P NMR spectroscopy might be useful for detecting and assessing the severity of cardiac rejection.…”
Section: Pohostmentioning
confidence: 99%